Kesalahan Pemahaman Siswa Sekolah Dasar dalam Menerjemahkan Soal Matematika - Aurelia, Davina; Ekawati, Ratna; Arifin, Slamet (Edumatica : Jurnal Pendidikan Matematika, 2024)
Comprehension is the foundation of problem-solving; without proper understanding, students will struggle to solve problems correctly. This research aims to identify specific types of mathematical comprehension errors in primary school students based on indicators from Newman's theory. By using Newman's error analysis framework, the study gives a detailed, step-by-step look at how students lose comprehension. This research was conducted using a descriptive qualitative method with three third-grade students as subjects, selected based on their level of mathematical ability (high, medium, low) determined through a diagnostic test. The results of the data analysis show that across the three student ability levels analyzed, the data revealed distinct patterns in the types of comprehension breakdowns encountered. High-performing students demonstrated minimal comprehension errors, successfully identifying key information. In contrast, mid-level students exhibited more significant issues linking the available information. The lowest-performing students showed the most fundamental misunderstandings, incorrectly identifying basic facts. These findings imply the need for a teaching approach that emphasizes contextual understanding and the development of mathematical literacy in comprehending story-based problems. Integrating evidence-based methods like problem-based learning, which have been shown to improve mathematical literacy in primary students, could help address the comprehension challenges observed in this study.